2022
DOI: 10.1038/s41467-022-30663-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and simultaneous capture of iodine and methyl iodide achieved by a covalent organic framework

Abstract: Radioactive molecular iodine (I2) and organic iodides, mainly methyl iodide (CH3I), coexist in the off-gas stream of nuclear power plants at low concentrations, whereas few adsorbents can effectively adsorb low-concentration I2 and CH3I simultaneously. Here we demonstrate that the I2 adsorption can occur on various adsorptive sites and be promoted through intermolecular interactions. The CH3I adsorption capacity is positively correlated with the content of strong binding sites but is unrelated to the textural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
148
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(165 citation statements)
references
References 62 publications
16
148
0
1
Order By: Relevance
“…After 20 hours, it was 1.573 times the original weight. This value is the highest adsorption capacity for iodomethane vapor reported to date (Figure 2c, Table S2) [12–15] . Moreover, the gel was easily recovered after adsorption.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…After 20 hours, it was 1.573 times the original weight. This value is the highest adsorption capacity for iodomethane vapor reported to date (Figure 2c, Table S2) [12–15] . Moreover, the gel was easily recovered after adsorption.…”
Section: Resultsmentioning
confidence: 60%
“…However, the high cost of silver and the limited loading of silver atoms in zeolite hinder their large‐scale application [7–11] . Although many organic materials, including metal–organic frameworks (MOFs), [3, 12] porous organic polymers (POPs), [13] and covalent‐organic frameworks (COFs), [14, 15] provide large surface areas and abundant active sites for efficient iodomethane deposition, their complicated manufacturing processes and still limited deposition capacity prohibit their further application. In addition, polymeric adsorbents for iodomethane adsorption are mainly based on the chemical reaction between the iodomethane and their functional groups, resulting in poor recyclability.…”
Section: Introductionmentioning
confidence: 99%
“…This value is the highest adsorption capacity for iodomethane vapor reported to date (Figure 2c, Table S2). [12][13][14][15] Moreover, the gel was easily recovered after adsorption. The recycling experiments showed that the adsorption capacity of iodomethane vapor decreased only slightly after five cycles, demonstrating good stability of the pyridine/TPC-cPS gel for adsorption and conversion of iodomethane vapor (Figure 2d).…”
Section: Forschungsartikelmentioning
confidence: 98%
“…However, the high cost of silver and the limited loading of silver atoms in zeolite hinder their large-scale application. [7][8][9][10][11] Although many organic materials, including metal-organic frameworks (MOFs), [3,12] porous organic polymers (POPs), [13] and covalent-organic frameworks (COFs), [14,15] provide large surface areas and abundant active sites for efficient iodomethane deposition, their complicated manufacturing processes and still limited deposition capacity prohibit their further application. In addition, polymeric adsorbents for iodomethane adsorption are mainly based on the chemical reaction between the iodomethane and their functional groups, resulting in poor recyclability.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Therefore, new attempts are designed to explore new matrix materials to have an affinity with iodine and solve the critical problem with iodine organic batteries. [21] Porous materials, or porous media, have long been iodine-hosted materials and explored by scientists worldwide. Hydrogen-bonded organic frameworks (HOF) are potential materials with a low-cost, recyclable, mental-free nature, less exothermic advantages, and more straightforward connectivity options.…”
Section: Introductionmentioning
confidence: 99%